Nontuberculous mycobacteria by metagenomic next-generation sequencing: Three cases reports and literature review - Liu, Ying; Ma, Xiaoxu; Chen, Jiajun; Wang, Huifen; Yu, Zujiang (Frontiers in Public Health, 2022)
Background The incidence of nontuberculous mycobacterial lung disease (NTM-LD) is increasing worldwide. The diagnosis and treatment of non-tuberculous mycobacterium pulmonary disease is a huge challenge, especially NTM-LD has similar clinical manifestations to tuberculosis, which is prone to misdiagnosis and mistreatment. Early and correct diagnosis and treatment can greatly improve the prognosis of patients. Case Presentation In 2020, three patients were diagnosed with nontuberculous mycobacterium (NTM) infection by metagenomic next-generation sequencing (mNGS). Both cases 1 and 2 were negative by conventional methods, while mNGS detected NTM pathogens. Case 3 NTM was detected by both traditional testing methods and mNGS, but blood mNGS could accurately determine which NTM infection was caused. Case 1 and Case 2 were significantly improved after anti-NTM treatment, but case 3 had a poor prognosis due to serious underlying diseases. Conclusions The mNGS may be a more rapid and sensitive test than conventional testing methods in diagnose NTM-LD. If mNGS detect NTM infection, anti-NTM infection treatment is recommended to improve patient outcomes. Through these findings, we hope that mNGS will provide some help in the clinical diagnosis of NTM infection. Key words: nontuberculous mycobacteria, nontuberculous mycobacterial lung disease, mNGS, diagnose, treatment.